Hayatını Vakıflara Vakfeden, Y. Mimar-Mühendis Prof. Dr. Yılmaz Önge - Bayram, Sadi (Vakıflar Genel Müdürlüğü, 2015)
1961 yılında mimar olarak girdiği Vakıflar Genel Müdürlüğü’nde, Ali Saim Ülgen’in vefatından sonra O’nun yerine geçmiş, bir yandan da doktora yapmaya başlamış, 1971 yılına kadar Vakıflar’daki görevini sürdürmüştür. Sonrasında üniversiteye geçmiş, profesörlüğe kadar yükselmiştir. Makalemizde, Yılmaz Önge’nin Vakıflar’daki çalışmalarına değinilerek, yapmış olduğu yayınlarının dökümü verilecektir.

After the death of Ali Saim Ülgen, Yılmaz Özge started to work at the Directorate General of Foundations, instead of Ülgen, in 1961. He continued his duty until 1971 whilst studying on his doctorate. Afterwards, he continued his career as an academician. The essay tells about his projects at the Directorate General of Foundations and a list of his publications.
Devoting a Lifetime to the Directorate General of Foundations, Architect-Civil Engineer Prof. Dr. Yılmaz Önge
Keywords: Yayın; Vakıf çalışmaları; Doktora; Mimar; Publication; Foundation projects; Doctorate; Architect